2016
DOI: 10.1016/j.hpb.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

The significance of underlying cardiac comorbidity on major adverse cardiac events after major liver resection

Abstract: Background: The risk of postoperative adverse events in patients with underlying cardiac disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…9,17,22 Another important observation of this study was the decreasing proportion of ALPPS patients with cardiovascular disease. Although prevalent cardiovascular disease was not an element of the prestage 1 risk prediction model, 15 the negative impact of this comorbidity on postoperative outcome has been well documented in major liver surgery 23 and might be also a contributing factor of risk adjustment in the present study.…”
Section: -Day Mortalitymentioning
confidence: 68%
“…9,17,22 Another important observation of this study was the decreasing proportion of ALPPS patients with cardiovascular disease. Although prevalent cardiovascular disease was not an element of the prestage 1 risk prediction model, 15 the negative impact of this comorbidity on postoperative outcome has been well documented in major liver surgery 23 and might be also a contributing factor of risk adjustment in the present study.…”
Section: -Day Mortalitymentioning
confidence: 68%
“…In the present study, patients taking statins had a higher prevalence of co‐morbidities such as DM, HTN, IHD and previous stroke. Preoperative factors such as DM, cardiac co‐morbidity and CKD are reported to have a negative influence on the overall outcomes after liver resection. A meta‐analysis documented that DM was associated with a significantly higher risk of overall complications, postoperative infections and liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis documented that DM was associated with a significantly higher risk of overall complications, postoperative infections and liver failure. Previous studies have documented that the presence of cardiac co‐morbidities led to a higher risk of 30‐day mortality also in non‐cardiac and major liver surgery. In the present analysis, similar effects were reported with diabetes, IHD and CKD, which all had a negative impact on 90‐day mortality ( Table S1, supporting information).…”
Section: Discussionmentioning
confidence: 99%
“…Schroeder et al reported that analyzing 587 patients undergoing LR from the American College of Surgeons-National Surgical Quality Improvement Program (ACS-NSQIP) database, overall TE after LR were at 3.6% [34] . Another research of 5,227 LRs from ACS-NSQIP database showed that the rate of critical cardiac complications including myocardial infarction and cardiac arrest after LR was at 4.8% in patients with underlying cardiac disease [35] . The present study demonstrated that the incidence of perioperative TE was maintained at 1.5% overall and at 1.9% in patients with continued APT, a relatively low rate compared to the previous report.…”
Section: Discussionmentioning
confidence: 99%